MODIFIED SWEEP ALGORITHM FOR ROUTE SELECTION IN PUBLIC BUS ROUTING PROBLEM USING FUZZY DATA - Gunadi Widi Nurcahyo; Alexyusandria alexyusandria (Teknik Elektro Politeknik Negeri Padang, 2012)
This paper investigates public bus route selection where demand is uncertain and evaluates the role of fuzzy logic in the MSA. The uncertain demand data are presented in linguistic form and transformed into fuzzy numbers. The crisp values obtained by the fuzzy logic are used to replace the exact demand in selecting best routes. The patterns of fuzzy data are presented to show capability of fuzzy data in representing exact data.